Chinese public opinion on Japan's nuclear wastewater discharge: A case study of Weibo comments based on a thematic model. (15th June 2022) - Pu, Xujin; Jiang, Qianyun; Fan, Bi
Abstract: Japan's plan to dump nuclear wastewater into the sea has generated a tremendous amount of discussion on social media due to the potential wide-ranging impact. To our knowledge, few studies have mined social media platforms to assess similar pollution concerns. We use the Octopus Collector to collect online textual data regarding "Japan's plan to dump nuclear wastewater into the sea" from Sina Weibo since April 13, 2021. After the posts from Sina Weibo were preprocessed, user opinions were analyzed using natural language processing. We used a naive Bayes classifier for sentiment analysis and latent dirichlet allocation (LDA) to extract and cluster topics from the posts, allowing for users' related opinions to be mined and analyzed. The study found that there were three major themes in terms of public concern: nuclear pollution and marine ecology, seafood imports and food safety, and international responsibility and public ethics. In our emotional analysis, we found that most people expressed negative emotions about the plan. However, there was also a positive emotional aspect because, with the release of relevant information and the popularization of knowledge, the public has been able to have a rational discussion about the consequences of this event, and the topic includes a focus on positive factors such as environmental protection and sustainable development. For this reason, the government and relevant agencies should keep up-to-date with the latest news of the incident to further raise public awareness and lead the public to a rational discussion to avoid excessive negative emotions. Graphical abstract: Image 1 Highlights: This study explored the public opinion towards the Japan's dumping nuclear wastewater event from social media. The sentiment analysis and LDA were employed to perform the quantitative analysis for public opinion. Public concerns about nuclear pollution and marine ecology, seafood imports and food safety, and international responsibility and public ethics. The emotional analysis found that most people expressed negative emotions about the plan. The government should keep up-to-date with the latest news of the incident to further raise public awareness.